2000
DOI: 10.4315/0362-028x-63.5.563
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Ultraviolet Light for Reducing Escherichia coli O157:H7 in Unpasteurized Apple Cider

Abstract: This study examined the efficacy of UV light for reducing Escherichia coli O157:H7 in unpasteurized cider. Cider containing a mixture of acid-resistant E. coli O157:H7 (6.3 log CFU/ml) was treated using a thin-film UV disinfection unit at 254 nm. Dosages ranged from 9,402 to 61,005 microW-s/cm2. Treatment significantly reduced E. coli O157:H7 (P < or = 0.0001). Mean reduction for all treated samples was 3.81 log CFU/ml. Reduction was also affected by the level of background microflora in cider. Results indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
105
3
4

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(119 citation statements)
references
References 20 publications
7
105
3
4
Order By: Relevance
“…But the stringent optical properties of liquid foods do not allow using most of these commercial units in the processing of these foods. The efficiency of UV-C treatment is highly affected by the reduced penetration depth as a result of the presence of solutes and particles (Wright, Sumner, Hackney, Pierson, & Zoecklein, 2000). Different types of UV reactors have been designed to overcome this limitation.…”
Section: Introductionmentioning
confidence: 99%
“…But the stringent optical properties of liquid foods do not allow using most of these commercial units in the processing of these foods. The efficiency of UV-C treatment is highly affected by the reduced penetration depth as a result of the presence of solutes and particles (Wright, Sumner, Hackney, Pierson, & Zoecklein, 2000). Different types of UV reactors have been designed to overcome this limitation.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, nonthermal processing techniques present an alternative method for juice processors to produce a minimally processed food with few and minor quality and organoleptic changes. UV irradiation is a nonthermal process that has shown its ability to inactivate pathogens in apple cider (15,16,32,35). Recent studies have demonstrated that doses of Ն6,500 W s/cm 2 were sufficient to achieve a 5-to 6-log reduction factor of E. coli in apple cider (26).…”
mentioning
confidence: 99%
“…UV irradiation is effective against a number of microorganisms that may be present in drinking water (3,26), including C. parvum oocysts (5). UV irradiation has been effective in the reduction of Escherichia coli O157:H7 in unpasteurized apple cider (20,25), and Harrington and Hills (13) demonstrated that cider exposed to UV for 54 showed no alterations in flavor quality when held at 22°C for up to 35 days. This study examined the effectiveness of using a CiderSure 3500A apparatus for UV irradiation to inactivate C. parvum oocysts in fresh apple cider.…”
mentioning
confidence: 99%